Effect Of Turmeric Extract (Curcuma Domestical) On Egg Hatchability and Survival Larvae of Pomfret Fish (Colossoma Macropomum) - Zulfahmi Zulfahmi; Dedi Fazriansyah Putra; Iko Imelda Arisa; Muhammad Muhammad (Jurnal Kelautan dan Perikanan Indonesia, 2023)
The success factor in the cultivation of pomfret (Colossoma macropomum) is related to cultivation techniques, from parent selection to the quality of eggs at hatching. Hatching media must be free from parasites, in the form of bacteria, fungi and other disturbances that cause eggs to die. Parasite attacks on eggs can be prevented, one of which is natural ingredients that are safe to use such as turmeric (Curcuma domestical). The purpose of this study was to test the effectiveness of turmeric extract (Curcuma domestical) on egg hatchability and survival rate of pomfret fish (Colossoma macropomum) larvae. This study was structured using a completely randomized design (CRD) consisting of 5 treatments with 4 replications, namely: treatment A (Without C. domestical Extract), Treatment B (Concentration 5 ml/L C. domestical Extract), Treatment C (Concentration 10 ml/L C. domestical Extract) treatment D (Concentration 15 ml/L C. domestical Extract) and treatment E (Concentration 20 ml/L C. domestical Extract). The results showed that soaking pomfret eggs with a concentration of turmeric extract (Curcuma domestical) 15 ml/l gave a significant effect on egg hatchability by 58,25% and larval survival by 87,86%. The conclusion of this study is that soaking with turmeric extract at a concentration of 15 ml/L is not too significant for egg hatchability and survival of pomfret larvae.Keywords: Curcuma domestical extract, pomfret fish, egg hatchability, survival rate